2018
DOI: 10.1021/acsami.8b16832
|View full text |Cite
|
Sign up to set email alerts
|

Coadsorption of a Monoclonal Antibody and Nonionic Surfactant at the SiO2/Water Interface

Abstract: ZL and FP made equal contributions AbstractDuring the formulation of therapeutic monoclonal antibodies (mAbs), nonionic surfactants are commonly added to attenuate structural rearrangement caused by adsorption/desorption at interfaces during processing, shipping and storage. We examined the adsorption of a mAb (COE-3) at the SiO 2 /water interface in the presence of pentaethylene glycol monododecyl ether (C 12 E 5 ), polysorbate 80 (PS80-20EO) and a polysorbate 80 analogue with 7 ethoxylates (PS80-7EO). Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…We show that the behaviour of the mAb and its constituent fragments at the oil/water interface is distinct from that reported previously at air/water and SiO 2 /water interfaces. [20][21][22][23] Our work thus paves the way for future studies directly utilizing PDMS oil to measureing the exact interfacial adsorption of the mAb and its constituent fragments and examining the effects of ionic strength, pH, surfactant co-adsorption, etc., which will advance our understanding of interfacial effects during mAb fill-finish processes and injection device selection. The "straight-through" method is used measure to ( ), the attenuation per unit length of the oil.…”
Section: Summaryconclusionmentioning
confidence: 96%
See 1 more Smart Citation
“…We show that the behaviour of the mAb and its constituent fragments at the oil/water interface is distinct from that reported previously at air/water and SiO 2 /water interfaces. [20][21][22][23] Our work thus paves the way for future studies directly utilizing PDMS oil to measureing the exact interfacial adsorption of the mAb and its constituent fragments and examining the effects of ionic strength, pH, surfactant co-adsorption, etc., which will advance our understanding of interfacial effects during mAb fill-finish processes and injection device selection. The "straight-through" method is used measure to ( ), the attenuation per unit length of the oil.…”
Section: Summaryconclusionmentioning
confidence: 96%
“…This structural feature is consistent with our previous observed COE-3 conformation adsorbed at the air/water 21 and hydrophilic silica/water interfaces. 22 In their QCM-D study of how several mAbs adsorbed to interfaces coated with hydrophobic silanes, Wiseman and Frank also concluded that monolayers of globular mAbs had been formed at the surface. 27…”
Section: Reflectivity Data Fitted To a One-layer Modelmentioning
confidence: 99%
“…A study by Kim et al [77] showed that polysorbates were able to inhibit protein adsorption but did not result in a protein/surfactant complex with an overall lower surface activity. To add to this, Li et al [78] have recently shown that PS 80 and C 12 E 5 could not prevent COE-3 adsorption at the SiO 2 /water interface. When a polysorbate 80 analogue with 7 ethoxylates (PS80-7EO) was used, it co-adsorbed but did not affect the equilibrated amount of adsorption from COE-3.…”
Section: The Sio 2 /Water Interfacementioning
confidence: 99%
“…Protein adsorption onto solid substrates is a widespread phenomenon, and its prevention is critical for proper functioning of medical devices and implants, as well as in bioseparation and other applications involving surfaces prone to contamination. The adsorption of proteins in these cases is largely of a nonspecific nature, and there is little control over the structure and composition of the adsorbed protein layer. When proteins from blood are adsorbed onto the surfaces of medical implants, the interfacial processes could undermine device integration at an early stage, trigger adverse cellular responses, and compromise the device’s performance and fate.…”
Section: Introductionmentioning
confidence: 99%
“…Specular NR is capable of quantitative determination of the thickness and uniformity of an interfacial layer with subnanometer sensitivity along the surface normal direction. ,,,− It effectively determines how the volume fraction (ϕ) of the layer varies with the distance perpendicular to the interface. The technique has been widely used in determining the interfacial layer structure of a variety of soft matters such as surfactants, peptides, ,,,,, proteins, antibodies, , DNAs, , polymers, and lipids. , As an example system, we employed a set of peptoid peptidomimetic polymers (PMPs) that we have previously demonstrated to prevent protein adsorption and cell attachment above certain chain length-dependent critical grafted chain densities. ,, PMPs form an excellent model brush system because of their exact chain lengths controlled by solid phase synthesis. , …”
Section: Introductionmentioning
confidence: 99%